INFLUENCE OF FOOD ADEQUACY ON ENROLMENT IN ECE CENTRES IN TURKANA CENTRAL SUB COUNTY, TURKANA COUNTY, KENYA - Erukudi, Locha; Edabu, Paul (African Journal of Education and Practice, 2020)
Purpose: This study sought to establish the influence of SFP on children enrolment in early childhood education centers in Turkana Central Sub-County, Kenya. Specific objective was to establish the influence of food adequacy on enrolment in ECE centres in Turkana Central Sub County, Turkana County, Kenya. Methodology: The study was based on Maslow hierarchy of needs, the program theory and liberal egalitarian theory. The study used a mixed research method. The study adopted the cross-sectional research design. The target population was 250 schools, 78 teachers and head teachers and 5,000 parents in pre-schools in Turkana Central Sub County. The study used purposive sampling to select respondents. The sample size of the study was 150 schools, 60 teachers and head teachers and 357 parents. Primary data was gathered by use of questionnaires and interviews guides. Secondary data consisted of report forms of pre-schoolers. Quantitative information was analyzed using descriptive statistics which was computed using SPSS version 21. Qualitative data was analyzed using content analysis. Multiple regressions were done to analyze the influence of SFPs on children enrolment in ECDE centres in Turkana Central Sub County. Findings: The study found that food adequacy significantly and positively relate with children enrolment in ECE centres in Turkana Central Sub County, Turkana County, Kenya. Food adequacy had statistically significant effect of school enrolment in ECD (Î² = 0.415, P = 0.005). It implies that food adequacy significantly and positively relate with children enrolment in ECE centres in Turkana Central Sub County, Turkana County, Kenya. This implies that increasing food adequacy will lead to increase in children enrolment in ECE centres in Turkana Central Sub County, Turkana County, Kenya. Unique contribution to theory, practice and policy: The study therefore recommends the government to increase food supply to ensure adequacy. There is need to continue supply of balanced diet to children because it improves their growth and learning. Some of the children are from very poor families and during school holidays they suffer because of lack of food; the study therefore recommends orphans, poor and disabled to be fed even during holidays.